An automated maintainability prediction tool integrated with Computer Aided Design - Lockett, Helen L.; Arvanitopoulos-Darginis, K. (Elsevier, 2017)
Design for maintainability is an important aspect of aircraft design, with maintenance representing 10 – 25% of the direct operating cost of an aircraft [1]. Design for Maintainability incorporates many aspects including assembly/ disassembly time, accessibility, visibility and ergonomics and it can be challenging for design engineers to consider at the design stage due to the time taken and specialist knowledge required. There are a number of existing tools that can be used to assess individual aspects of maintainability but these were mostly developed as paper based tools that require the designer to visualise the maintenance task while studying the engineering drawings or observing an operator performing the task. This paper presents an automated maintainability prediction tool that is integrated with the CATIA v5 Computer Aided Design software. The tool allows the designer to rapidly estimate the maintenance corrective time for a maintenance task utilising a CATIA product model as its input. It uses elemental maintenance action standard times from MIL-HDBK-472 Procedure V to estimate maintenance task times, and RULA, OWAS and LBA ergonomics methods to apply a time penalty based on the operator ergonomics during the task. In this paper the maintainability prediction tool will be tested on a range of simple aircraft maintenance tasks to assess how accurately it can predict maintenance corrective times. The results from the tool are compared to experimental data from physical trials for each maintenance task and the results discussed.
Keywords: Aircraft Design; Maintainability Prediction; Computer Aided Design; Ergonomics; MIL-HDBK-472